Organizational policies to encourage bicycles in urban mobility in Porto Alegre, Rio Grande do Sul - Matzembacher, Daniele Eckert; Nascimento, Luis Felipe Machado do (Revista de Administração da UFSM, 2018)
The aim of this study was to identify the incentive policies developed by organizations in Porto Alegre/RS to encourage the use of bicycle as a mean of transportation. We also investigated whether these incentives are linked to social and socioenvironmental management programs. Finally, we examined if these influenced workers on the decision to use cycling to commute to work. The survey found that bicycle racks, changing rooms, showers, lockers, tool kit and promotional marketing are some of the components of policies to encourage the use of bicycles. It was observed that most of the studied organizations did not link their social and environmental policies with the practices to encourage the use of bicycles. Regarding cyclists, it was observed that policies encouraging the use of bicycles have positive results in choosing this mean as urban mobility. This work shows the relevance to introduce means of transport that promote better physical and mental health to the population, to help address mobility problems, the use of public spaces, and contribute to reducing the emission of air pollutants.